Pelatihan Video Iklan Produk dan Strategi Pemasaran Digital di SMKN 2 Kalianda - Fikri Hamidy; Donaya Pasha; Heni Sulistiani; Yuri Rahmanto; Masnia Rahayu (Universitas Teknokrat Indonesia, 2023)
The activity aims to introduce marketing strategies with the concept of school promotion through workshops (basic training) to increase students' interest in being creative through directed steps with strategic marketing concepts: awareness, interest, desire and action of customers or potential customers. The training activities were attended by 126 students of SMKN 2 Kalianda through product advertisement video sessions and digital marketing strategy sessions. The product advertising video training and digital marketing strategy went well and received a good reception from SMKN 2 Kalianda as a PKM partner at the Universitas Teknokrat Indonesia. The competencies expected after the training are knowledge, skills and attitudes for the knowledge, skill and attitude product advertisement video sessions sequentially with an average value of 88%, 88% and 81% respectively. It can be stated that the competence of students is good and good enough to master video product advertisements. As for the digital marketing strategy session after the training, namely knowledge, skills and attitudes respectively, the average values are 91%, 90% and 89%, respectively. It can be stated that the competence of students is very good for mastering digital marketing strategies. If we look at the enthusiasm of the participants, we conclude that students from vocational high schools have great potential for technology-based mastery and digital marketing systems